Quantification of alcohol drinking patterns in mice - Eisenhardt, Manuela; Spanagel, Rainer (Addiction biology, 2015)
The use of mice in alcohol research provides an excellent model system for a better understanding of the genetics and neurobiology of alcohol addiction. Almost 60 years ago, alcohol researchers began to test strains of mice for alcohol preference and intake. In particular, various voluntary alcohol drinking paradigms in the home cage were developed. In mouse models of voluntary oral alcohol consumption, animals have concurrent access to water and either one or several concentrated alcohol solutions in their home cages. Although these models have high face validity, many experimental conditions require a more precise monitoring of alcohol consumption in mice in order to capture the role of specific strains or genes, or any other manipulation on alcohol drinking behavior. Therefore, we have developed a fully automated, highly precise monitoring system for alcohol drinking in mice in the home cage. This system is now commercially available. We show that this drinkometer system allows for detecting differences in drinking behavior (i) in transgenic mice, (ii) following alcohol deprivation, and (iii) following stress applications that are usually not detected by classical home-cage drinking paradigms. In conclusion, our drinkometer system allows disturbance-free and high resolution monitoring of alcohol drinking behavior. In particular, micro-drinking and circadian drinking patterns can be monitored in genetically modified and inbred strains of mice after environmental and pharmacological manipulation, and therefore this system represents an improvement in measuring behavioral features that are of relevance for the development of alcohol use disorders.